Crowd Analyzer using Trilateration and Keep Alive Signals - I, Kethsia; U, Domesan (Journal of ISMAC, 2024)
Tracking mobile phones in a specific area is crucial for assessing population density and understanding crowd dynamics. Traditional methods rely on Wi-Fi and GPS, but offline techniques like cell tower triangulation offer valuable insights even in areas with limited connectivity. By analyzing the number of mobile phones present, estimated through trilateration using signals from the phone’s keep-alive signal, one can accurately estimate the crowd size. This information aids in urban planning, transportation management, event organization, and business strategies. Empowered with such data, decision-makers can optimize resource allocation, enhance safety measures, and improve overall societal well-being through informed decision-making.